2015
DOI: 10.1002/2015jb012262
|View full text |Cite
|
Sign up to set email alerts
|

Universal scaling of the formation factor in clays: Example from the Nankai Trough

Abstract: Electrical conductivity is a fundamental characteristic describing how strongly a network opposes flow of electrical current. In fully water‐saturated porous media the conductivity, represented by the formation factor, is mainly controlled by porosity, connectivity of the conducting phases, and the tortuosity of electrical current paths. Previous work has shown that universal scaling derived from percolation and effective medium theories accurately describes the relationship between formation factor and porosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…However, it is seen that the fit at lower fluid conductivity is not as good as at higher one. The reason is that the assumption of the conduction current path in parallel may be not truly valid at low electrolyte concentration [Daigle et al, 2015]. Figure 8 shows the ratio of the electrical conductivity of the glass bead samples to that with ± 10 % uncertainty.…”
Section: Effect Of the Textural Parameters Of The Porous Mediummentioning
confidence: 99%
“…However, it is seen that the fit at lower fluid conductivity is not as good as at higher one. The reason is that the assumption of the conduction current path in parallel may be not truly valid at low electrolyte concentration [Daigle et al, 2015]. Figure 8 shows the ratio of the electrical conductivity of the glass bead samples to that with ± 10 % uncertainty.…”
Section: Effect Of the Textural Parameters Of The Porous Mediummentioning
confidence: 99%
“…As before, we use the two Archie's law formulations F = φ −m and F = τ /φ. In addition, we consider the percolation-theory model F = (φ − φ c ) −t (e.g., [31,52,53]), in order to evaluate whether the notion of a critical porosity φ c helps to interpret data corresponding to low-porosity fractured porous media with sparse fracture networks. Note that in this case, the estimated value of φ c is restricted to lie between 0 and the minimum porosity of the considered fracture family.…”
Section: Results At the Fracture Percolation Thresholdmentioning
confidence: 99%
“…Thus, it is difficult to predict the relationship between p t and porosity based on the surface area to volume ratio. To this point, both Hunt () and Daigle, Ghanbarian, et al () observed a trend of p t decreasing as porosity decreased in soils and marine muds. A detailed understanding of the phenomena governing these observations is lacking, and yet is critically important for understanding subsurface fluid flow.…”
Section: Introductionmentioning
confidence: 90%